Considerations over the Italian road bridge infrastructure safety after the Polcevera viaduct collapse: past errors and future perspectives (Fracture and Structural Integrity, 2018)
In the last four years, Italy experienced the collapse of five road bridge: Petrulla viaduct (2014), Annone (2016) and Ancona (2017) overpasses, Fossano viaduct (2017) and Polcevera (2018) bridge.Although for deeply different reasons, the collapses occurred can all been gathered into the same common cause: the (lack of) knowledge of the effective structural condition, a serious problem that affects existing constructions.As it will be shown in the paper, different problems such as missing of the as-built designs, an appropriate construction and movement precautions, a heavy vehicle checking, and a material decay monitoring can nevertheless be addressed as an inadequate knowledge of what is happening to/in the structure.In the first section, the paper will report a short description of the failures for the five bridges, while in the second part a main set of problems involved in bridge safety and maintenance will be discussed. Finally, in the third part, a review on innovative and peculiar investigation and monitoring techniques will be illustrated. The collected results can shed new light on future perspectives for the Civil Engineering sector, sector that has to be ready for facing the challenges of preservation, restoration and/or replacement of the existing infrastructural constructions, worldwide.
Keywords: Bridge collapse; Existing infrastructural constructions; Prestressed concrete failure; Bridge robustness; Innovative monitoring